2021
DOI: 10.1186/s12983-021-00413-0
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian breeding phenology influences offspring size and response to a common wetland contaminant

Abstract: Background Increases in temperature variability associated with climate change have critical implications for the phenology of wildlife across the globe. For example, warmer winter temperatures can induce forward shifts in breeding phenology across taxa (“false springs”), which can put organisms at risk of freezing conditions during reproduction or vulnerable early life stages. As human activities continue to encroach on natural ecosystems, it is also important to consider how breeding phenolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…In common toads Bufo bufo in the United Kingdom, warmer than average temperatures correlated with decreased body condition and survival (Reading 2007). Recent work on wood frogs showed that phenological shiZs can expose individuals to colder temperatures and resulted in lower tolerance of offspring to pollutants like NaCl (Buss et al 2021). Collectively these data suggest that in some species, warming can induce cryptic cost of breeding plasticity in multiple life stages that are not immediately apparent if looking at phenological variables alone (see Blaustein et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In common toads Bufo bufo in the United Kingdom, warmer than average temperatures correlated with decreased body condition and survival (Reading 2007). Recent work on wood frogs showed that phenological shiZs can expose individuals to colder temperatures and resulted in lower tolerance of offspring to pollutants like NaCl (Buss et al 2021). Collectively these data suggest that in some species, warming can induce cryptic cost of breeding plasticity in multiple life stages that are not immediately apparent if looking at phenological variables alone (see Blaustein et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Increased winter precipitation resulting from climate change can benefit some amphibians (Benard 2015), but extreme weather events and advanced phenologies are likely to negatively impact others (Blaustein et al . 2010; Buss et al 2021). In a review of the impacts of increased droughts and extreme precipitation, Walls et al .…”
Section: Introductionmentioning
confidence: 99%
“…The effects of climate change on amphibians are threatening the survival of numerous species by altering phenological cues for spring emergence (Buss et al 2021) and shifting available temperature ranges surrounding biological processes (Fontaine et al 2018), forcing species to rapidly adapt or migrate to remain within thermal optima (Enriquez-Urzelai et al 2019). For example, amphibians have a bi-phasic (aquatic and terrestrial) lifestyle and many of their biological and reproductive processes rely on narrow environmental temperature and moisture ranges, and so amphibians are especially sensitive among vertebrates to climate induced stressors and abrupt changes in land use (Zellmer et al 2020).…”
Section: Climate Changementioning
confidence: 99%
“…Among the known responses to climate change, shifts in phenology or the timing of key life-history events of organisms are the most well documented (Cohen et al, 2018;Roslin et al, 2021;Visser & Both, 2005;Walther et al, 2002). Often, the timing of important phenological events (e.g., reproduction) matches periods of high resource availability to support high fitness and survival costs (Bradshaw & Holzapfel, 2007;Buss et al, 2021;Forchhammer et al, 1998;Helm et al, 2013;Reed et al, 2013;Walther et al, 2002). Fitness costs of reproduction are often attributed to the increased energetic demands of maintaining and developing reproductive organs and behaviors (Audzijonyte & Richards, 2018), and survival costs are incurred from increased predation risk (Kelt et al, 1995).…”
Section: Introductionmentioning
confidence: 99%